Clinoptilolite- and glauconite-based sorbents for lead removal from natural waters - Stepova, Kateryna; Konanets, Roman (Journal of Environmental Engineering and Landscape Management, 2024)
The aim of the research is to determine the effect of heat treatment and microwave irradiation on the sorption properties of a natural clinoptilolite and glauconite to Pb2+ ions. To improve the sorption capacity the samples were heat treated at 550 °C for 3 hours or microwaved at 790 W for 30 minutes. The XRD and XRF analysis present the content of investigated samples and prove the increase in the sorption capacity after treatment. After contact with Pb, its content in the natural clinoptilolite increased to 2.66%, and in the thermally treated – to 6.035%. The PbO content in natural glauconite increased to 3.9%, but after microwaving it reached 5.2% of the total sample weight. Heat treatment is useful for improving the sorption capacity of clinoptilolite, and microwave irradiation can significantly increase the adsorption capacity of glauconite.